PHYSIOTHERAPY MANAGEMENT FOR STROKE PATIENT ON STATIC BALANCE ABILITY: A CASE STUDY - Maulidia, Kamila; Wahyuni, W; Rahayu, Umi Budi (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Stroke is a disease that causes damage to the brain due to infarction or bleeding in the blood vessels that supply blood to the brain, resulting in a lack of oxygen and glucose supply to brain tissue. In stroke patients, the general symptom that appears is weakness on one side of the limb which will affect the ability to balance. Handling efforts that can be done are to offer single leg stance and walking training. Case Presentation: The patient is 67 years old, female with a job as a housewife. Currently the patient is able to carry out activities well at home, but the patient often complains that his left side of the limb still feels heavy and his balance decreases when standing or walking. Management and Outcome: The study was conducted 3 times a week in 4 weeks. Mini Mental State Examination (MMSE) was given to determine the cognitive level of respondents. Evaluation is carried out every week using the Functional Reach Test (FRT). Physiotherapy management that used single leg stance and walking training which was carried out for 4 weeks resulted in an increase in static balance in the patient. Discussion: Single leg stance and walking training can increase proprioceptive input which will increase the ability to support on the injured side so as to produce a balanced weight bearing. In addition, the provision of this exercise can train visual, somatosensory, vestibular and proprioceptive which will maintain an upright body position during walking and improve the correct gait pattern so as to improve balance ability.